2017
DOI: 10.1049/mnl.2016.0813
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic activity towards oxygen reduction reaction of laminar nanocomposite LaNb 2 O 7 /Co III TMPyP prepared via the exfoliation/restacking method

Abstract: The laminar lanthanum niobate KLaNb 2 O 7 with perovskite structure was intercalated with cationic cobalt (III) tetrakis-5, 10, 15, and 20-(N-methyl-4-pyridyl) porphyrin using the exfoliation/restacking method. The as-prepared material was characterised by several analytic methods including X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and infrared microscopy. The exfoliation/restacking process was monitored and proved by the change of zeta potential, and the cyclic voltamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…For example, Xu et al reported that a laminar lanthanum niobite (KLaNb 2 O 7 ) could be used to incorporate the CoTMPyP by exfoliation and restacking method. [227] As expected, the interlayer space of the composite increased. The exfoliated LaNb O 7 sheets maintained their layered structure after functionalization with porphyrin.…”
Section: Functionalization Of Alternative 2d Materials Using Porphyrinssupporting
confidence: 72%
“…For example, Xu et al reported that a laminar lanthanum niobite (KLaNb 2 O 7 ) could be used to incorporate the CoTMPyP by exfoliation and restacking method. [227] As expected, the interlayer space of the composite increased. The exfoliated LaNb O 7 sheets maintained their layered structure after functionalization with porphyrin.…”
Section: Functionalization Of Alternative 2d Materials Using Porphyrinssupporting
confidence: 72%